Core Java volume 1 -- Fundamentals - Horstman, Cay S.; Cornell, Gary (Upper Saddle River, New Jersey : Prentice-Hall, 2013)
Fully updated to reflect Java SE 7 language changes, Core Java$1!"(B, Volume I$1 (BFundamentals, Ninth Edition, is the definitive guide to the Java platform. Designed for serious programmers, this reliable, unbiased, no-nonsense tutorial illuminates key Java language and library features with thoroughly tested code examples. As in previous editions, all code is easy to understand, reflects modern best practices, and is specifically designed to help jumpstart your projects. Volume I quickly brings you up-to-speed on Java SE 7 core language enhancements, including the diamond operator, improved resource handling, and catching of multiple exceptions. All of the code examples have been updated to reflect these enhancements, and complete descriptions of new SE 7 features are integrated with insightful explanations of fundamental Java concepts.s
1. An introduction to Java (Java as a programming platform ; The Java "white paper" buzzwords ; Java applets and the Internet ; A short history of Java ; Common misconceptions about Java) -- 2. The Java programming environment (Installing the Java development kit ; Choosing a development environment ; Using the command-line tools ; Using an [IDE] integrated development environment ; Running a graphical application ; Building and running applets) -- 3. Fundamental programming structures in Java (A simple Java program ; Comments ; Data types ; Variables ; Operators ; Strings ; Input and output ; Control flow ; Big numbers ; Arrays) -- 4. Objects and classes (Introduction to object-oriented programming ; Using predefined classes ; Defining your own classes ; Static fields and methods ; Method parameters ; Object construction ; Packages ; The class path ; Documentation comments ; Class design hints) -- 5. Inheritance (Classes, superclasses, and subclasses ; Object: the cosmic superclass ; Generic array lists ; Object wrappers and autoboxing ; Methods with a variable number of parameters ; Enumeration classes ; Reflection ; Design hints for inheritance). 6. Interfaces and inner classes (Interfaces ; Object cloning ; Inner classes ; Proxies) -- 7. Graphics programming (Introducing Swing ; Creating a frame ; Positioning a frame ; Displaying information as a component ; Working with 2D shapes ; Using color ; Using special effects for text ; Displaying images) -- 8. Event handling (Basics of event handling ; Actions ; Mouse events ; The AWT [abstract window toolkit] event hierarchy) -- 9. User interface components with Swing (Swing and the model-view-controller design pattern ; Introduction to layout management ; Text input ; Choice components ; Menus ; Sophisticated layout management ; Dialog boxes) -- 10. Deploying applications and applets (JAR files ; Java Web Start ; Applets ; Storage of application preferences) -- 11. Exceptions, assertions, logging and debugging (Dealing with errors ; Catching exceptions ; Tips for using exceptions ; Using assertions ; Logging ; Debugging tips ; Tips for troubleshooting GUI [graphic user interface] programs ; Using a debugger). 12. Generic programming (Why generic programming? ; Defining a simple generic class ; Generic methods ; Bounds for type variables ; Generic code and the virtual machine ; Restrictions and limitations ; Inheritance rules for generic types ; Wildcard types ; Reflection and generics) -- 13. Collections (Collection interfaces ; Concrete collections ; The collections framework ; Algorithms ; Legacy collections) -- 14. Multithreading (What are threads? ; Interrupting threads ; Thread states ; Thread properties ; Synchronization ; Blocking queues ; Thread-safe collections ; Callables and futures ; Executors ; Synchronizers ; Threads and Swing) -- Appendix: Java keywords.
Includes bibliographical references and index.
Keywords: JAVA (COMPUTER PROGRAM LANGUAGE)